ANALISIS KELEMBAGAAN PENYULUHAN PERTANIAN DI KABUPATEN KUANTAN SINGINGI - Dicky Hendy Putra; Roza ' Yulida; Eri ' Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The extention are contribute in order to increase the productivity, production and income of the farming communities. But lately, the existence of extention institution are decrease that cause by vary factors. In Riau Province, the implementation of agricultural extention in Kuantan Singingi district at level of sub-district are under management of sub-department or Unit Pelaksanaan Teknis Dinas (UPTD). This research are intend to reviewing the vision and mission, to analyze the duty and fuction based on existing structure on the institution of each department at Kuantan Singingi district, reviewing the existing rule and policy on each department at Kuantan Singingi district. The result of the research shows that all department has vision and mission which is descript the performance that will be achieve for the next 5 year period since the vision and mission that published. Basically, the vision and missionthat had made has shows the success from the time to the time, but still there are problems on achieve vision and mission. Meanwhile from programa agricultural extention, there is 1 department that doesn’t make the programa of agricultural extention, which is on Fisheries department. Point out of the fifth departments has 1 Person as Head of Department, 1 Person as Secretary, 3 Person as Head of Divisions and some several person as section. Rule and policy that made by each department at Kuantan Singingi district, basically emphasize to increase the quality of administration of the institutional, public management, and the improvement of the knowledge of human resources as well as at the department environment or on the  farm level.